Griots at war : conflict, conciliation, and caste in Mande - Hoffman, Barbara G. (Indiana University Press, 2000)
In 1985, while she was an apprentice griot or jelimuso, Barbara G. Hoffman saw and recorded a remarkable event that took place in the small town of Kita, Mali. For four days, thousands of griots from all parts of the Mande world gathered together to talk, sing, and make music in celebration of the opening of the new Hall of Griots and the installation of the recently named Head Griot. This unprecedented assembly, unheard of in the history of the Mande, also marked the end of the two-year long 'War of the Griots'; a deadly conflict fought with the tools of the griot verbal masters - words, reputations, and sorcery. "Griots at War" captures griots in action as they made speeches, sang songs of praise, and danced in honor of their renewed unity. Hoffman's discerning transcription and examination of the speeches not only reveals the oratorical skills of griots, but their skill in using history, metaphor, religion, proverbs, and praise to mend a community that had been torn apart by war. But Hoffman discovers a startlingly keen edge to the griots' words. Who intervenes, and how, when war breaks out in the griot community? The speeches made at Kita expose both griots and nobles engaged in behaviours that were strikingly unexpected of people of their status. Hoffman shows that griot public oratory also functions to delineate the boundaries of griot castes and to persuade other castes to recognise and respect what gives each caste its unique identity. While the verbal art of griots has been well documented in the form of epic poetry, "Griots at War" brings their formidable linguistic abilities to the fore as they negotiate, reestablish, and assert their cultural power. This exceptional book offers surprising and important insights into the multiple meanings of Mande culture, caste, and identity